Political technologies: structural and functional indifference - O. N. Zabuzov (Управление)
The problem field of understanding the essence of political technologies has been defined in the article. The nature of political technologies has been analysed. Semantic components of political technologies have been studied. The place and meaning of the adjective “political” in the semantic content of political technologies have been determined, the conditions for the acquisition of political functions by social technologies have been indicated. Numerical uncertainty in relation to political technologies has been removed. The peculiarity of adopting political technologies in their activities and other social subjects that differ from political actors has been shown. The author’s vision of the essence of the content of political technologies has been proposed.The structure of political technologies in the context of its political indifference has been studied. Various authors’ approaches of scientists to determining the structure of political technologies have been analysed. The author’s vision of the structure of political technologies from the point of view of their political indifference has been offered. We refered to components of the structure of political technologies: the goal setting, the conceptual component, the content component, the procedural component, the performance-evaluation component. A brief description of the components of the structure of political technologies has been given.The functions of political technologies from the point of view of their political indifference have been explored. The methodological bases, that served as the basis for determining these functions are political interests which are the political driver that encourages political actors to use a particular political technology or a combination of them have been offered.. The most significant, in our opinion, functions of political technologies have been highlighted. Examples of individual political technologies that most clearly characterize the selected political functions have been given. These examples show the functional indifference of political technologies.The functional indifference of political technologies has been shown: in terms of their content, structure and functions, political technologies are "indifferent" to the political process, to the person who uses them.